DESCRIPTION OF THE STRUCTURE AND MORPHMETRI OF THE SMALL INTESTINE OF BALI DUCK AT DIFFERENT AGES - Reston, Umi; Suatha, I Ketut; Heryani, Luh Gde Sri Surya; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
The Bali duck is one of the original Indonesian germplasm whose distribution is endemic in Bali. This study aims to determine the anatomical structure, histology, and morphometry of the small intestine of Bali ducks at different ages. In this study, samples of the small intestine of Bali ducks aged 1 month, 3 months, and 5 months were used as many as 18 male Bali ducks. Bali ducks were obtained from one of the duck farms in Mengwi District, Badung Regency, Bali Province. Sampling of the small intestine was carried out in three parts, namely the duodenum, jejunum and ileum, then the organs were fixed with 10% NBF which was then made histological preparations with HE staining. The research results are presented in the form of qualitative and quantitative descriptive. The results showed that the anatomical structure of the small intestine, namely the duodenum, jejunum and ileum, had the same composition, boundaries and shape in ducks of different ages, while the histological structure of the small intestine, namely the duodenum, jejunum and ileum, was composed of four layers, namely the tunica mucosa, tunica submucosa. tunica muscularis and the outermost is the tunica serosa. Small intestine morphometry results in Balinese ducks at different ages had a significant difference at 1 and 3 months, 1 and 5 months, whereas in ducks at 3 and 5 months they were not so significant in the duodenum, jejunum and ileum.  Based on the research conducted, it can be concluded that there is no change in the anatomical structure in terms of composition, boundaries, and shape, while histologically , each Balinese duck small intestine is composed of four layers including the tunica mucosa, tunica submucosa, tunica serosa and serosa, while based on the results of intestinal morphometry fine bali ducks have significant differences in each age of bali ducks both in the duodenum, jejunum and ileum, so it is necessary to do further research on female ducks and perform histomorphometry on each layer.